Generic model of optimal body composition prediction of elite male volleyball - Dopsaj, M.; Anicic, Z.; Markovic, S.; Majstorovic, N.; Necic, G. (XXI Scientific Conference "FIS COMMUNICATIONS 2018" in physical education, sport and recreation (Nis, Serbia, October 18-20, 2018), 2018)
It is known that body composition is a general indicator of the condition of the human organism and it is influenced by the effects of numerous factors, such as diet, health condition, level of physical activity, stress and other. One of the most important factors for the body composition is the individual's level of physical activity. It is known that, under the direct influence of a certain sport, the structure of the athlete's body adapts to the requirements of that sport. Purpose of the research is to find a generic model of optimal body composition for top volleyball players. Subjects sample consists of 22 elite volleyball players aged 26.86 +/- 3.12 years (Min-Max = 2-33 years), National team members. Measurement of body composition was carried out by a standard procedure using the method of electrical multichannel bioimpedance (BIA). The total number of variables is 17, as follows: primary variables (7), variables partialized in relation to longitudinality (5), variables partialized in relation to volume (4) and specific body structure variable (1). Number of variables in the morphological structure of the body is reduced by factor analysis. Three variables (factors) were isolated in final factor iteration: the percentage of body fat (PBF), the total weight of the free fat component (FFM), and the protein mass index (PMI). For the purposes of evaluation and prediction of morphological status of elite volleyball players, a multidimensional score (Morph_Point_SCORE) was defined using Mathematical modeling and Multivariate Regression Analysis. The research was conducted on elite volleyball players and provides a more detailed picture of the morphological characteristics of top athletes. Thus, research results could serve as reference values for future research that would investigate the area of elite male volleyball body composition. The practical significance of the research is that it provides, to both coaches and other practitioners, additional information about which body structure corresponds to a defined model of body composition.